2010
DOI: 10.1021/jm100925m
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, Radiolabeling, and in Vivo Evaluation of Carbon-11 Labeled N-[2-[4-(3-Cyanopyridin-2-yl)piperazin-1-yl]ethyl]-3-methoxybenzamide, a Potential Positron Emission Tomography Tracer for the Dopamine D4 Receptors

Abstract: Here we describe the design, synthesis, physicochemical, and pharmacological evaluation of D4 dopamine receptor ligands related to N-[2-[4-(4-chlorophenyl)piperazin-1-yl]ethyl]-3-methoxybenzamide (2). Structural features were incorporated to increase affinity for the target receptor, to improve selectivity over D2 and sigma1 receptors, to enable labeling with carbon-11 or fluorine-18, and to adjust lipophilicity within the range considered optimal for brain penetration and low nonspecific binding. Compounds 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 61 publications
1
14
1
Order By: Relevance
“…Permeabilized platelets from New Zealand albino rabbit was the source of VMAT2 (Cesura et al, 1990). Tissue from rat brains (with the cerebellum and brain stem removed) was the source of cannabinoid CB 1 , GHB, opioid (m, d, and k), and muscarinic (M 1 , M 4 , and M 5 ) receptors, and membranes were prepared as described previously for CB 1 receptors (Lacivita et al, 2010). Table 1.…”
Section: Preparation Of Membranes For Radioligand Binding Assaysmentioning
confidence: 99%
“…Permeabilized platelets from New Zealand albino rabbit was the source of VMAT2 (Cesura et al, 1990). Tissue from rat brains (with the cerebellum and brain stem removed) was the source of cannabinoid CB 1 , GHB, opioid (m, d, and k), and muscarinic (M 1 , M 4 , and M 5 ) receptors, and membranes were prepared as described previously for CB 1 receptors (Lacivita et al, 2010). Table 1.…”
Section: Preparation Of Membranes For Radioligand Binding Assaysmentioning
confidence: 99%
“…) was not able to visualize D 4 receptor in monkey brain, but it showed fast kinetics, and it did not show nonspecific binding, suggesting that the lipophilicity of 1e can be targeted to minimize nonspecific binding. It should be noted that, for 1e, we observed a significant difference between experimental log P value measured by the pH metric technique (log P ¼ 2.55) [29] and the calculated one (ClogP ¼ 1.5). A recent study by Kügler et al [33] has reported a significant correlation between the experimentally determined log P values of four potential D 4 4 -receptor PET radiotracer, we modified further the structure of the compounds listed in Table 1 with the aim to obtain new compounds that would have: a) high affinity for D 4 receptor (K i 1.5 nm) b) low affinity for dopamine D 2 and D 3 receptors (K i > 500 nm) c) a good brain penetration as predicted by log P values in an optimal range as compound 1e.…”
mentioning
confidence: 53%
“…Moreover, it is difficult to predict, and it has been correlated with lipophilicity of the substance [25 -28]. Recently we have reported the rational design of a set of benzamide derivatives structurally related to the high-affinity D 4 ligand 1a as potential PET radiotracers (compounds 1a -1f and 2a -2f, Table 1) [29], which showed moderate lipophilicity in the ClogP range of 2.5 -3.5 that is considered optimal for adequate brain penetration without an excessive level of nonspecific binding [30 -32]. Among the target compounds, derivative 1e ( (Fig.…”
mentioning
confidence: 99%
“…Recently, we reported on the rational design of a set of high-affinity D 4 receptor benzamide derivatives [42] engineered to have low off-target affinity, low non-specific binding, and lipophilicity within the optimal range (c logP range of 2.5 -3.5) for brain penetration by passsive diffusion [43 -45]. The derivative [ 11 C]2 ( Fig.…”
mentioning
confidence: 99%
“…The derivative [ 11 C]2 ( Fig. Intense [ 11 C]2 PET image signals in monkey were observed in the region of the posterior eye with little to no background signal in other parts of the brain including the cingulate, entorhinal, occipital, and cerebellar cortices, as well as the striatum and hippocampus [42]. Intense [ 11 C]2 PET image signals in monkey were observed in the region of the posterior eye with little to no background signal in other parts of the brain including the cingulate, entorhinal, occipital, and cerebellar cortices, as well as the striatum and hippocampus [42].…”
mentioning
confidence: 99%